¿Cómo determinar la densidad de plantas y la necesidad de nitrógeno óptima para maíz? - Videla Mensegue, Horacio Rogelio; Pagnan, Luis Federico; Razquin, Claudio; Pietrantonio, Julio; Magra, Maria Sofia; Vaia, María Paula; Allovatti, Sofia; Feresin, Patricio Fernando; Muñoz, Sebastián Andrés (AAPRESID, 2024)
Poster